2020
DOI: 10.1002/celc.202000427
|View full text |Cite
|
Sign up to set email alerts
|

Dense Sandwich‐like Na2Ti3O7@rGO Composite with Superior Performance for Sodium Storage

Abstract: Sodium titanate (Na 2 Ti 3 O 7 ) has been considered as a promising anode in sodium-ion batteries (SIBs) because of its low working voltage, high energy density and low cost. However, low electronic and ionic conductivity become the major obstacles to affect the improvement of its electrochemical performance.Here, based on the high specific surface area and high conductivity of reduced graphene oxides (rGO), a dense sandwich-like structure was built through a facile hydrothermal route. The Na 2 Ti 3 O 7 @rGO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Clearly, the electrochemical properties of F-NTO HSs, both in cycle life and rate performances, were much superior to those obtained in other NTO involving works (with detailed performances compared in Table S2†). 18–23,28,31,32,47,52–61 The above analysis further demonstrated the advantages of the F-NTO HS electrode upon cycling, even at an extraordinary high rate, implying its feasibility as a high capacity anode with good kinetics behavior for SIBs. Moreover, excellent electrochemical performances could be found for the NVP@C|F-NTO HS full cell.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Clearly, the electrochemical properties of F-NTO HSs, both in cycle life and rate performances, were much superior to those obtained in other NTO involving works (with detailed performances compared in Table S2†). 18–23,28,31,32,47,52–61 The above analysis further demonstrated the advantages of the F-NTO HS electrode upon cycling, even at an extraordinary high rate, implying its feasibility as a high capacity anode with good kinetics behavior for SIBs. Moreover, excellent electrochemical performances could be found for the NVP@C|F-NTO HS full cell.…”
Section: Resultsmentioning
confidence: 67%
“…14 Moreover, it showed the lowest Na intercalation potential compared with other reported insertion-type oxides (0.3 vs. Na/Na + ), [15][16][17] which contributed to higher working voltage and energy density for practical application. 18 Notwithstanding, the NTO anode was still challenged by the following disadvantages: 19,20 (i) the collapse of NTO layers due to the huge volume change upon Na + insertion/ extraction nally led to fast capacity decay; 21 (ii) low electronic conductivity (induced by the wide bandgap of 3.7 eV) and poor Na + diffusion kinetics (3.5 Â 10 −12 cm 2 s −1 ) resulted in sluggish e − /Na + transportation.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that incorporating 2D active materials into 2D material interlayers such as graphene and MXene as spacers could effectively prevent the natural restacking of 2D active materials. This approach resulted in enhanced electrochemical performances for MnO 2 nanosheets/graphene, 19 Sb nanosheets/graphene, 20 Na 2 Ti 3 O 7 nanosheets/graphene, 21 phosphorene nanosheets/MXene, 22 and MoS 2 nanosheets/graphene. 23 Because of the superior electrical conductivity afforded by the carbon matrices, which ensures excellent electron transfer in the charge/discharge operation, the electrochemical performance in terms of specific capacity has been greatly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, with the large‐scale application of LIBs, the increasing shortage of lithium resources has restricted their development. Therefore, the scientific intention has been attracted to sodium‐ion batteries (SIBs) because of their low cost and sodium‐rich resources [11–12] . Nevertheless, the radius of lithium ions is smaller than that of sodium ions, which causes that the commercial electrode materials for LIBs, such as graphite materials, are not suitable for SIBs [13–14] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the scientific intention has been attracted to sodium-ion batteries (SIBs) because of their low cost and sodium-rich resources. [11][12] Nevertheless, the radius of lithium ions is smaller than that of sodium ions, which causes that the commercial electrode materials for LIBs, such as graphite materials, are not suitable for SIBs. [13][14] Electrode materials largely determine the electro-chemical performance of batteries.…”
Section: Introductionmentioning
confidence: 99%